Micro- and Mesoporous Carbide-Derived Carbon-Selenium Cathodes for High-Performance Lithium Selenium Batteries - Lee, Jung Tae; Kim, Hyea; Oschatz, Martin; Lee, Dong-Chan; Wu, Feixiang; Lin, Huan-Ting; Zdyrko, Bogdan; Cho, Won Il; Kaskel, Stefan; Yushin, Gleb (WILEY-V C H VERLAG GMBH, 2015)
Nanocomposites of selenium (Se) and ordered mesoporous silicon carbide-derived carbon (OM-SiC-CDC) are prepared for the first time and studied as cathodes for lithium-selenium (Li-Se) batteries. The higher concentration of Li salt in the electrolytes greatly improves Se utilization and cell cycle stability. Se-CDC shows significantly better performance characteristics than Se-activated carbon nanocomposites with similar physical properties. Se-CDC also exhibits better rate performance and cycle stability compared to similarly produced sulfur (S)CDC for Li/S batteries.
Keywords: GROUND-STATE PROPERTIES; ELECTRONIC-STRUCTURE; MIGRATION ENERGY; PORE-SIZE; SULFUR; LI; 1ST-PRINCIPLES; HALIDES; CELLS; IONS